Pengaruh Pendidikan Kewirausahaan, Lingkungan Keluarga Dan Ekspetasi Pendapatan Terhadap Minat Berwirausaha Mahasiswa Akuntansi Universitas Hindu Indonesia - Antari, Ni Putu Nova; Putra, I Putu Deddy Samtika; Pratiwi, Ni Putu Trisna Windika (UNHI Press, 2025)
Entrepreneurial interest is an innate tendency that drives individuals to develop and create businesses with the ability to organize, manage, take risks, and sustainably grow the enterprises they establish. It reflects a drive to become active, creative entrepreneurs who seize business opportunities and play a crucial role in managing and developing their ventures. This study aims to analyze the influence of entrepreneurial education, family environment, and income expectations on entrepreneurial interest. The population of this study consists of all active undergraduate students of the Accounting Department in the Faculty of Economics, Business, and Tourism at Hindu Indonesia University, who have completed the entrepreneurship course, totaling 328 students. The sampling method used in this study is non-probability sampling with slovin. The data analysis method employed is Partial Least Square (PLS) analysis. The results show that entrepreneurial education has a positive and significant effect on entrepreneurial interest, the family environment has a positive and significant effect on entrepreneurial interest, and income expectations have a positive and significant effect on entrepreneurial interest.